Analisis Isolasi Panas Pada Casing Turbin Gas Tipe M701D Di PLTGU Grati - Vendy Antono; Syaiful Achmad (Sekolah Tinggi Teknik - PLN, 2016)
The function of the gas turbine casing insulation is to reduce the rate of heat transfer from the gas turbine to the surrounding air, preventing the risk of fire, prevent the risk of operator safety and other hazards. Based on the findings of a team of thermography in PLTGU Grati, it is known there are many points of leakage of heat (hot spots) in a gas turbine casing. One effect of this is the emergence of hot spots burning wires and thermocouple terminal BPTdi gas turbine, which led into a gas turbine trip. Several methods can be used to handle the emergence of hot spots in the insulation casing, is to replace the insulating material, adding thickness (Δx) isolasiserta modify the shape and position of isolation. After studying a variety of sources, it is known that the ceramic fiber insulation blankets is a type of casing the best and most appropriate to isolate the gas turbine casing in PLTGU Grati. In addition, of several methods that can be used to handle hot spots in the insulation casing, then the most effective way is to modify the shape and rearrange the position of the insulation to fit the shape of casing gas turbine (adjusted for standartnya), so there is no longer hot spot appear, so that the gas turbine can avoid the risk of trip.